Gene expression profiling and molecular characterization of antimony resistance in Leishmania amazonensis. - Rubens L do Monte-Neto; Adriano C Coelho; Frédéric Raymond; Danielle Légaré; Jacques Corbeil; Maria N Melo; Frédéric Frézard; Marc Ouellette (Public Library of Science (PLoS), 2011)
BACKGROUND: Drug resistance is a major problem in leishmaniasis chemotherapy. RNA expression profiling using DNA microarrays is a suitable approach to study simultaneous events leading to a drug-resistance phenotype. Genomic analysis has been performed primarily with Old World Leishmania species and here we investigate molecular alterations in antimony resistance in the New World species L. amazonensis. METHODS/PRINCIPAL FINDINGS: We selected populations of L. amazonensis promastigotes for resistance to antimony by step-wise drug pressure. Gene expression of highly resistant mutants was studied using DNA microarrays. RNA expression profiling of antimony-resistant L. amazonensis revealed the overexpression of genes involved in drug resistance including the ABC transporter MRPA and several genes related to thiol metabolism. The MRPA overexpression was validated by quantitative real-time RT-PCR and further analysis revealed that this increased expression was correlated to gene amplification as part of extrachromosomal linear amplicons in some mutants and as part of supernumerary chromosomes in other mutants. The expression of several other genes encoding hypothetical proteins but also nucleobase and glucose transporter encoding genes were found to be modulated. CONCLUSIONS/SIGNIFICANCE: Mechanisms classically found in Old World antimony resistant Leishmania were also highlighted in New World antimony-resistant L. amazonensis. These studies were useful to the identification of resistance molecular markers.